Time trends in HPV vaccination according to country background: a nationwide register-based study among girls in Norway - Bjerke, Randi Dalene (BMC Public Health, 2021)
BACKGROUND: Since the human papillomavirus (HPV) vaccine was introduced in Norway in 2009, the vaccine uptake has increased. Whether this increase is similar regardless of the girls’ country background is unknown. We examined changes in HPV vaccine uptake from 2009 to 2014 and studied the impact of parental education and income on HPV vaccine uptake according to country background. METHODS: Girls in the first six birth cohorts (1997–2002) eligible for HPV vaccination were identified through the National Registry. Information on HPV vaccination, country background and socioeconomic factors was extracted from the Norwegian Immunisation Registry and Statistics Norway. Risk differences (RDs) and confidence intervals (CIs) were estimated with linear binomial regression. A total of 177,387 girls were included in the study. RESULTS: The HPV vaccine uptake increased from 72.5% in 2009 to 87.3% in 2014. The uptake increased for girls in all country background categories. Highest vaccine uptake was observed in girls with East−/South-East Asian background, 88.9% versus 82.5% in the total population. Vaccine uptake decreased slightly with increasing parental education, RD = − 1.6% (95% CI: − 2.3% to − 0.8%) for highest compared with lowest education level. In contrast, the uptake increased with increasing household income, RD = 4.9% (95% CI, 4.3 to 5.5%) for highest compared with lowest quintile. Parental education had largest impact in girls with Asian background, RD = − 8.1% (95% CI − 10.5% to − 5.6%) for higher vs lower education. The largest impact of household income was observed in girls with background from Middle East/Africa, RD for a 200,000 NOK increase in income was 2.1% (95% CI 1.2 to 3.0%). CONCLUSIONS: The HPV vaccine uptake differed with country background but increased over time in all country background categories. Moreover, the impact of education and income on vaccine uptake differed with country background. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10877-8.